2001
DOI: 10.1046/j.1365-2362.2001.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A and high‐density lipoprotein cholesterol: serum markers of inflammation in sarcoidosis and other systemic disorders

Abstract: Hypocholesterolemia has been observed in several inflammatory diseases such as rheumatoid arthritis, myeloproliferative disorders, systemic lupus erythematosus and sarcoidosis. Serum amyloid A is an acute-phase reactant that is related to the high-density lipoprotein cholesterol. This review discusses the relationship between the activation of the cells of the monocyte-macrophage system, determined by the serum amyloid A levels, and the lipid metabolism, measured as alterations in plasma lipoprotein concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 69 publications
3
26
1
2
Order By: Relevance
“…As sarcoidosis is an inflammatory disease, it has been expected to observe increased values of hsCRP, ACE (11,12) and SAA compared to controls (13,14) and our results were in agreement with these findings (Table I). Increased concentrations of SAA may be a consequence of either increased production of proinflammatory cytokines that stimulate hepatic production of SAA (11) or activated cells in granulomas that also produce SAA (15).…”
Section: Discussionsupporting
confidence: 92%
“…As sarcoidosis is an inflammatory disease, it has been expected to observe increased values of hsCRP, ACE (11,12) and SAA compared to controls (13,14) and our results were in agreement with these findings (Table I). Increased concentrations of SAA may be a consequence of either increased production of proinflammatory cytokines that stimulate hepatic production of SAA (11) or activated cells in granulomas that also produce SAA (15).…”
Section: Discussionsupporting
confidence: 92%
“…(Gabay & Kushner 1999;Bahk et al 2010). The conversion of SAA to apolipoprotein A-I and A-II increases the catabolism of HDL, and changes the distribution of HDL by inhibiting lecithinÀcholesterol acetyltransferasemediated lipidation of serum cholesterol (Steinmetz et al 1989;Kumon et al 1993;Salazar et al 2001). …”
Section: Relationship Between the Urine Protein Profile And Lipid Metmentioning
confidence: 99%
“…SAA is potentially involved in the pathogenesis of several chronic inflammatory diseases: it is the precursor of amyloid A protein deposited in amyloid A amyloidosis, and has also been implicated in the pathogenesis of atherosclerosis and rheumatoid arthritis. 23,24 SAA may be closely related to poor patient outcomes, including left ventricular systolic dysfunction, cardiac rupture and mortality in acute myocardial infarction. 25,26 Some studies have suggested that the elevation of SAA may be associated with acute allograft rejection of the kidney, 27-30 liver 31 and heart.…”
Section: Identification Of Markers For Pirs After Cbt By Seldi-tof Msmentioning
confidence: 99%